Diseño agronómico e hidráulico para la implementación de un sistema de riego por aspersión en el cultivo de banano (Mussa paradisiaca) en el cantón La Maná recinto San Eduardo. - Caiza Punina, Jessy Maribel (2022)
The present investigation and implementation were developed in San Eduardo precinct, La Maná canton; the general objective was to determine the agronomic and hydraulic design for the implementation of a sprinkler irrigation system for the cultivation of banana (Mussa paradisiaca). This work began with the realization of a physical analysis of soils and the investigation of the agrometeorological parameters of the closest station to the project area. This information served as input to calculate the water demand of the crop which maximum value resulted in 3.02 mm/day, so the agronomic design and irrigation programming were defined with an irrigation frequency of 6 days and a required gross lamina of 24.16 mm. An impact sprinkler with an operating flow rate of 1.3 m3/h and a reach diameter of 24.4 mm was selected. The irrigation area is rectangular with a spacing between sprinklers of 12 m and between laterals of 14 m, so achieving a rainfall of 7.74 mm/h that in an irrigation time of 3 hours, the required irrigation lamina is covered. For the hydraulic design, the topography of the property was carried out in order to know the area and the natural unevenness of the land, obtaining an area of 1.2 hectares that were subdivided into 3 sectors or irrigation modules, the network of pipes is constituted by the main conduction, lateral and sprinkler holder pipes; the determined diameters correspond to: 90 mm for the main pipe, the lateral holder pipe is 75 mm for 3 laterals, and 90 mm for 5 laterals; the sprinkler holder pipes are 40 mm for 5 sprinklers and 50 mm for 6 sprinklers. The pumping equipment that was defined for the project is a combustion pump with a minimum flow rate of 9.03 l/s, a manometric height of 70 mca, and a power superior to 16.6 HP. A quantification of materials and accessories required for the implementation of the irrigation system was carried out, resulting in a reference cost of 4426.27 dollars.